THE ROLE OF DEPRESSION, LONELINESS AND SUBJECTIVE WELL BEING IN PREDICTING ACADEMIC ACHIEVEMENT - Kose, ?brahim Alper (Institute of Advanced Engineering and Science, 2020)
Previous literature pointed out that there was a relationship between psychological constructs and students? academic achievement. In the frame of this basement, therelationships between psychological constructs;components of subjective well-being, loneliness, depression, and academic achievement were tested in a proposed model.As a research group, 488 university students in Bolu-Turkey were participated. Research data were examined by bivariate correlations and hierarchical multiple regression analysis. Results showed that depression wassignificant predictor of academic achievement. In addition, the impact of depression on students? achievement was enhanced by loneliness andSWB components? additive contribution was not significant. Depression and loneliness explained a substantial amount of variance in the prediction of academic achievement. These findings are discussed in the frame of related literature. As implications, higher education administrators, policy makers, academic staff should take in consideration that psychological constructs are related to student achievement. Counseling services should established or developed specifically at the universities.